Pattern formation in unstable viscous convective medium - Gushchin, I.V.; Kirichok, А.V.; Kuklin, V.M. (Вопросы атомной науки и техники, 2013)
The convection in a thin layer of liquid (gas) with poorly heat conducting boundaries and with temperature dependent viscosity are considered. The Proctor-Sivashinsky model is examined in order to study both the pattern formation and the second-order structural phase transitions as between patterns with translational invariance as well as between structures with broken translational invariance but keeping a long-range order. The influence of the temperature dependence of viscosity on the process of pattern formation and structure transformations is discussed. Is shown that the temperature dependence of viscosity inhibits structural transition leading to formation of square cells. Initiallyquasi-stable structure of convective rolls becomes stable under this condition. Розглянуто моделі опису конвекції в шарі рідини (газу) з границями, що погано проводять тепло, з урахуванням залежності в'язкості від температури. Обговорюється коректна модель Проктора-Сівашінского в рамках якої, можна описати як розвиток просторових структур так і структурно-фазові переходи другого роду між станами, що мають різну топологію та різний ступень порушення трансляційної інваріантності. Обговорюється вплив температурної залежності в'язкості на розвиток процесу формування структур і структурних трансформацій. Рассмотрены модели описания конвекции в слое жидкости (газа) с плохо проводящими тепло границами с учетом зависящей от температуры вязкости. Обсуждается корректная модель Проктора-Сивашинского в рамках которой можно описать как развитие пространственных структур, так и структурно-фазовые переходы второго рода между состояниями, обладающими разной топологией с разной степенью нарушений трансляционной инвариантности. Обсуждается влияние температурной зависимости вязкости на развитие процесса формирования структур и структурных трансформаций.